Evaluation Of Treatment Outcomes And Factors Associated With Unsuccessful Outcome Among Drug Resistant Tuberculosis Patients At Punjab, Pakistan - Massud, Asif (2023)
Pakistan ranks fourth globally in terms of drug-resistant Tuberculosis (DR-TB) burden. Treatment outcomes are greatly affected by patients’ epidemiological characteristics such as lifestyle, population density, baseline clinical parameters, drug resistance patterns and clinical practices to manage adverse drug reactions (ADRs) complications. Being a high-burden DR-TB country, Pakistan lacks prospective data about the impact of local epidemiology, resistance pattern, unsuccessful treatment outcomes, risk factors, and management of adverse drug reactions. A prospective study of 271 DR-TB patients enrolled and treated at Nishtar Medical University Hospital Multan was carried out to assess the baseline drug resistance, treatment outcomes and nature and frequency of ADRs. All DR-TB patients enrolled at the study site were eligible except pregnant women, children, and intellectually disabled patients.